Controllable morphologies and electrochemical performances of self-assembled nano-honeycomb WS2 anodes modified by graphene doping for lithium and sodium ion batteries. (February 2019) - Song, Yaochen; Liao, Jiaxuan; Chen, Cheng; Yang, Jian; Chen, Jinchen; Gong, Feng; Wang, Sizhe; Xu, Ziqiang; Wu, Mengqiang
Abstract: Self-assembled nano-honeycomb WS2 modified by graphene doping were prepared by improved one step hydrothermal method. In this hybrid structure, graphene plays a key role of transferring the morphology from the nanowire microporous spheres to graphene-supported nano-honeycomb plane structure, which has the larger the specific surface area and higher conductivity. This anode delivers the superb electrochemical performances of lithium/sodium ion batteries with high specific charge capacity (953.1/522.3 mAh·g −1 at 0.1 A·g −1 ), long cycling life (more than 350/200 cycles at 1 A·g −1 ), and high charge/discharge rates (up to 10/5 A·g −1 ). This nano-honeycomb structure WS2 composite anode with facile hydrothermal process, as well as superb electrochemical performances, makes it attractive for the potential applications in lithium/sodium ion batteries. Graphical abstract: Image 1